AN ANALYSIS OF FATWA NO. 141/DSN-MUI/VIII/2021 ON THE ESTABLISHMENT AND OPERATIONAL GOVERNANCE OF ISLAMIC COOPERATIVES: AN ISTIHSAN PERSPECTIVE - SYAIFUL ANWAR; Syaiful Bahri; Zainul Arif (Wasīlah: Journal Of Sharia Sciences, 2026)
This study examines Fatwa No. 141/DSN-MUI/VIII/2021 concerning the Guidelines for the Establishment and Operational Management of Islamic Cooperatives from the perspective of istihsan in Islamic jurisprudence. The study aims to analyze the normative framework and legal reasoning underlying the fatwa in regulating the institutional structure and operational governance of Islamic cooperatives in Indonesia. This research employs a qualitative approach using library research. The primary data sources include the Qur'an, Hadith, DSN-MUI fatwas, and classical Islamic jurisprudence literature, while secondary data sources consist of books, academic journals, and related documents on Islamic cooperatives and Islamic economic law. The findings indicate that Fatwa No. 141/DSN-MUI/VIII/2021 provides comprehensive guidelines for the establishment and operation of Islamic cooperatives through the implementation of sharia-based contractual mechanisms such as syirkah, mudharabah, wakalah, and ijarah. These mechanisms emphasize the principles of justice, transparency, cooperation, and the prohibition of riba, maysir, and gharar. From the perspective of istihsan, the cooperative model reflects a juristic preference that prioritizes public benefit (maslahah) and supports collective economic cooperation within Islamic legal principles. The study concludes that the fatwa strengthens the legal and institutional legitimacy of Islamic cooperatives while promoting ethical and sharia-compliant economic practices.